2017
DOI: 10.1002/aic.15657
|View full text |Cite
|
Sign up to set email alerts
|

A continuum‐approach modeling of surface composition and ternary component distribution inside low fat milk emulsions during single droplet drying

Abstract: Surface composition of dairy powders plays an important role in determining the functionality. However, the surface composition may be different from the bulk composition because of component migration during drying. In this study, a comprehensive mathematical model has been developed to describe the phenomena. To the best of our knowledge, it is the first mathematical model which predicts the dynamics of surface composition during drying. The model consists of a set of equations of conservation of mass of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Nevertheless, the gradient temperature inside the eggplant samples is essentially small which is also indicated by Ch_Bi (Chen and Peng, 2005) which is found to be about 0.002. The low gradients of temperature during drying of food materials are also reported previously (Putranto and Chen, 2015 a-c ;Putranto et al, 2017).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, the gradient temperature inside the eggplant samples is essentially small which is also indicated by Ch_Bi (Chen and Peng, 2005) which is found to be about 0.002. The low gradients of temperature during drying of food materials are also reported previously (Putranto and Chen, 2015 a-c ;Putranto et al, 2017).…”
Section: Resultssupporting
confidence: 76%
“…The spatial reaction engineering approach (S-REA) is used to model the convective drying of eggplant in this study. The details of the reaction engineering approach (REA) have been published previously (Chen and Putranto, 2013;Putranto and Chen, 2015 a,b ;2016;Putranto et al, 2017). The S-REA consists of a set of equations of conservation of heat and mass transfer in which the REA is used to describe the local evaporation rate.…”
Section: Mathematical Modelling Using the Spatial Reaction Engineerinmentioning
confidence: 99%
“…However, as shown in other studies, the reaction rate decreases at lower moisture contents due to limited molecular mobility (Schmitz‐Schug et al, 2014). This difference between the predicted and actual correlation between the reaction rate constants may lead to an overestimation of the extent of the Maillard reaction in the final product by the model, even though the segregation process tends to be completed at lower moisture contents (Putranto et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has been shown that the REA is not only able to model the evaporation of water but also volatiles (organic components) (Putranto & Chen, ). In addition, the REA has been applied to model the solute segregation inside dairy droplets (Putranto et al ., )…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that the REA is not only able to model the evaporation of water but also volatiles (organic components) (Putranto & Chen, 2016). In addition, the REA has been applied to model the solute segregation inside dairy droplets (Putranto et al, 2017) Due to the applicability of the REA so far, it is worthwhile to develop the REA-based model to represent the mass loss during cheese ripening. Although the REA has been proven to model the several challenging heat and mass transfer processes as described above, it is uncertain whether the REA is applicable to model the mass loss during cheese ripening because chemical and biological reactions may significantly alter the cheese structure.…”
Section: Introductionmentioning
confidence: 99%